Biopesticide Research and Product Development in Africa for Sustainable Agriculture and Food Security – Experiences From the International Centre of Insect Physiology and Ecology (icipe) - Akutse, Komivi S.; Subramanian, Sevgan; Maniania, Nguya; Dubois, Thomas; Ekesi, Sunday (Frontiers in Sustainable Food Systems, 2020)
Arthropod pests and vectors constrain the livelihood opportunities of people in Africa by debilitating production of crops and livestock and through transmission of vector-borne diseases. In the absence of effective alternative management options to tackle these pests and vectors, there is extensive dependence on synthetic pesticides for their management on crop and livestock systems, with significant negative impacts on animal and human health, and the environment. Biopesticides are effective and environmentally sustainable alternatives to synthetic pesticides. At the International Centre of Insect Physiology and Ecology (icipe), the Arthropod Pathology Unit (APU) was established for effective biopesticide research-for-development (R4D), underpinned by a large repository of arthropod pathogens, protocols for lab bioassays and field efficacy testing, and an effective public-private partnership to generate new biopesticide products. The focus of icipe's APU has gradually transformed from basic to applied research leading to innovative, commercial products. Among the insect pathogens, greater focus has been placed on fungi, especially Metarhizium anisopliae, against key crop and livestock pests. Presently, three biopesticides based on M. anisopliae strains researched by icipe have been commercialized by Real IPM (Thika, Kenya) and are used on 132,994 ha in sub-Saharan Africa, with registration of additional products against animal ticks and the fall armyworm Spodoptera frugiperda pending. Our R4D activities on arthropod pathogens increasingly include bacteria, microsporidia, entomopathogenic nematodes and viruses. Recently, icipe is expanding R4D toward plant endophytes and rhizosphere inhabitants. The Centre also embarked on understanding the diversity, roles and possible exploitation of insect symbionts in key plant pest and disease vectors. In addition, key entomopathogens of reared insects for human food and animal feed need to be identified and controlled through high hygiene standards during rearing. Further, research is aimed at integrating biopesticides not only with other integrated pest management (IPM) technologies but also with pollination services.